Midazolam Attenuates Esketamine-Induced Overactive Behaviors in Mice Before the Sedation, but Not During the Recovery - Chu, Qinjun; Mao, Meng; Bai, Yafan; Sun, Liwei; Zhang, Dongqing; Zheng, Ping; Jin, Xiaogao (Frontiers in Veterinary Science, 2022)
Esketamine showed more potency, more rapid recovery from anesthesia, and less psychotomimetic side effects when compared with ketamine. However, the patients still experience psychotomimetic side effects of esketamine. In order to investigate whether midazolam can attenuate the esketamine-induced overactive behaviors and neuronal hyperactivities, midazolam 0, 40, 80, and 120mg/kg combined with esketamine 50mg/kg were administrated on Kunming mice to assess the behaviors changes during anesthesia. The indicators, including action time, duration of agitation before sedation, duration of sedation, duration of pedal withdrawal reaction loss, duration of right reflex loss, duration of agitation during recovery, and recovery time, were monitored for up to 3-4 hours after intraperitoneal administration. The results demonstrated that midazolam 40, 80, and 120 mg/kg efficiently decreased the esketamine-induced overactive behaviors including ataxia, excitation and catalepsy before sedation. Midazolam and esketamine synergically improved the anesthesia quality assessed by Pedal Withdrawal Reaction and Righting Reflex. However, even high doses of midazolam were not able to suppress the esketamine-induced psychotomimetic effects during the recovery.